STRATEGI MANAJEMEN FILANTROPI GAYA BARU SOLO PEDULI KLATEN - Lathifah, Nuur Is; Widiastuti, Rindi Antika (IAIN Surakarta, 2019)
The purpose of this research is to describe the management strategies related to the management of philanthropy in the Solo Peduli Klaten, as well as community empowerment undertaken. This research uses descriptive method with management theory from Stephen P. Robbins and James A.F. Stoner. The result is known success in philanthropy management conducted by Solo Peduli by applying the four elements of management. The philanthrophy is done through donations from donated donations, as well as from zakat, infaq and alms prepared based on the work program that has been made. The Solo Peduli work program seeks to improve the welfare of the community in the fields of health, education, economics, social and religious as well as social.Keywords: Management; Preaching; Solo Peduli